PEMBERIAN ABU SEKAM PADI DAN JERAMI PADI UNTUK PERTUMBUHAN SERTA SERAPAN TANAMAN JAGUNG MANIS (Zea Mays L.) PADA TANAH ULTISOL DI KECAMATAN RANTAU SELATAN - Fitra Syawal Harahap; Hilwa Walida (JURNAL AGROPLASMA, 2020)
Provision of Rice Husk Ash and Rice Straw for Growth of Sweet Corn (Zea Mays L) in Ultisol Land in Rantau Selatan District Labuhan Batu District aims to determine the effect of various types of rice husk ash and rice straw for growth and nutrient uptake of Sweet Corn experimental methods. The method used in this study was compiled in a factorial randomized block design consisting of 2 factors with 3 replications. Treatment I: Giving rice husk ash (M) with 4 dose levels (g / 5 kg BTKO), namely: M0 (0), M1 (10 ), M2 (20) and M3 (30) and Treatment II: Giving rice straw (K) compost with 4 dose levels (g / 5 kg BTKO), namely: K0 (0), K1 (25), K2 (50), K3 (75). The data obtained were statistically analyzed based on analysis of variance on each observed variable that was measured and tested further for real treatment using the Duncan Multiple Range Test (DMRT) at the 5% level. The parameters measured consist of. Plant height (cm), Plant Dry Weight, Plant U uptake, Plant U Uptake. The results of this study indicate that the administration of rice straw compost has a significant effect in increasing plant height, plant dry weight, N uptake and P uptake while rice husk ash has a significant effect in increasing plant N uptake but has no significant effect in increasing plant height, plant dry weight and P uptake of plants. Keywords: husk ash, rice straw, growth, nutrient uptake, corn, Rantau selatan